A Simple Physical Model to Analyse the Direct Pressure Performance of a Wave Energy Harvester Based on a Dielectric Elastomer Generator - Omar M.A.; Zamri M.S.; Zakaria N.M.; Yasir A.S.H.Md.; Mukhtar A. (American Institute of Physics, 2025)
Dielectric elastomer generators (DEGs) are a kind of electrostatic flexible transducer that can transform the oscillating mechanical energy from various sources into usable electricity. Among the most promising uses of DEG is wave energy harvesting. DEGs are suited for harvesting mechanical energy from ocean waves due to their lightness, low cost, high energy density, and rapid responsiveness to mechanical shocks. At present, a simple and intriguing physical model of a dielectric elastomer-based wave energy converter is being constructed and analysed. The experiment's physical model activities, such as laboratory testing and wave tank tests, are discussed to demonstrate the development of the device scale and performance. Different wave heights are considered during the testing process. In addition, preliminary experimental results on the evaluation of a physical model for three distinct elastomer layers are presented. A self-priming circuit is then developed to increase the voltage and charge capacity of a DEG. According to the results, the elastomer diluent generated greater power. In addition, very small pressure is required to generate power. Therefore, the accumulated power produced in 120 seconds can be as high as 1.079 mW. Based on the results of the experiments that have been done, the DEG is a very good choice for the next generation of wave energy converters (WECs). ? 2024 American Institute of Physics Inc.. All rights reserved.